A Assessing The Quality of Learning Assessment in Islamic Theology and Ethics: A Psychometric and Cognitive-Level Analysis of Grade X Textbook Questions in Indonesian Islamic Senior High Schools - Azizah, Dalvah Nur (Department of Teacher Professional Education, Tarbiya and Teacher Training Faculty, UIN Sunan Gunung Djati Bandung, 2023)
This study aims to examine the quality of assessment items in the Grade X Islamic Theology and Ethics (Akidah Akhlak) textbook used in Indonesian Islamic senior high schools by analyzing their cognitive levels and classification into Lower Order Thinking Skills (LOTS), Middle Order Thinking Skills (MOTS), and Higher Order Thinking Skills (HOTS). The study employed a qualitative descriptive research design with document analysis as the primary data collection technique. The units of analysis consisted of 45 essay-type questions distributed across four chapters of the textbook. The findings reveal a strong dominance of LOTS-oriented items, with 39 questions (88%) categorized as LOTS, while only 3 questions (6%) reflected MOTS and 3 questions (6%) met the criteria for HOTS. In terms of cognitive level, most items were concentrated at the C2 (understanding) level, indicating limited opportunities for students to engage in analytical, evaluative, or creative thinking processes. These results suggest that the assessment items in the analyzed textbook have not yet adequately aligned with contemporary curriculum demands that emphasize higher-order thinking and 21st-century skills. The predominance of low-level cognitive questions may constrain students’ critical thinking development and reduce the effectiveness of assessment in Islamic education. Therefore, teachers, textbook authors, and curriculum developers are encouraged to redesign assessment tasks by incorporating more HOTS-oriented items to enhance cognitive challenge, pedagogical quality, and alignment with modern educational standards in Islamic senior high schools.